First record of the genus Berosus (Coleoptera: Hydrophilidae) in Crete island, Greece - Karaouzas, I.; İncekara, Ü. (ENTOMOLOGIA HELLENICA, 2011)
The first record of the genus Berosus Leach, 1817 (Coleoptera: Hydrophilidae) for Crete (Greece) is given. Adults of the collected specimens were identified as Berosus affinis Brullé, 1835. Photographs of the adults and larvae of the species and its habitat are presented, while some notes on its ecology and feeding behavior are provided.